Coping with a Money Crunch: Values, Goals, and Standards - Michael S. Gutter; Josephine Turner; Katey Walker (EDIS)
As a consumer, having an array of choices is usually a good thing. But having to make choices can also be a problem. New products, services, and ways of doing things are being developed all the time. It’s even more difficult to make decisions when you’re experiencing a money crunch. This revised 3-page fact sheet was written by Michael S. Gutter, Josephine Turner, and Katey Walker, and published by the UF Department of Family, Youth and Community Sciences, July 2012.